2021
DOI: 10.21817/indjcse/2021/v12i2/211202051
|View full text |Cite
|
Sign up to set email alerts
|

An LSTM Based CNN Model for Pomegranate Fruit Classification With Weight Optimization Using Dragonfly Technique

Abstract: Pomegranate is a widely grown plant in India. This highly beneficial fruit is infected by multiple pests and diseases which cause great economical losses. Different forms of pathogen diseases on leaf, stem and the fruits are present. Some of the diseases that affect pomegranate fruits are anthracnose, cercospora, heart rot and bacterial blight. There is a need for disease control strategies to incorporate timely action on the developed diseases. Thus, there is a need for intelligent and self-learning recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The experiment showed that this method had a maximum signalto-noise ratio of 52.8dB and a minimum error of only 0.19. Vasumathi M T and his team utilized the dragonfly algorithm to optimize the detection performance of long and short term convolutional networks, and applied the resulting hybrid algorithm to the identification of pests and diseases in pomegranate plants [11]. According to the test results, the classification accuracy of using long and short term convolutional networks alone was lower than that of networks optimized by the dragonfly algorithm, with the latter achieving a maximum accuracy of 99.1%.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment showed that this method had a maximum signalto-noise ratio of 52.8dB and a minimum error of only 0.19. Vasumathi M T and his team utilized the dragonfly algorithm to optimize the detection performance of long and short term convolutional networks, and applied the resulting hybrid algorithm to the identification of pests and diseases in pomegranate plants [11]. According to the test results, the classification accuracy of using long and short term convolutional networks alone was lower than that of networks optimized by the dragonfly algorithm, with the latter achieving a maximum accuracy of 99.1%.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to illegal structures, the attenuation of algorithms is also a problem that needs to be considered in BNSL.In the DO algorithm, the variation of its inertia weight w follows a linear function. Assuming max t as the maximum number of iterations, the mathematical expression of w is shown in formula (11). max (0.90.4) 0.9 t w t…”
Section: B Bnsl Based On Bdv Dragonfly Optimizationmentioning
confidence: 99%
“…Vasumathi dan Kamarasan,2021, melakukan penelitian dengan model CNN berbasis LSTM pada mengklasifikasikan buah delima menjadi dua kelas normal dan abnormal dengan optimasisasi Teknik capung, hasil eksperimen menunjukkan akurasi 92% dalam klasifikasi menggunakan teknik CNN-LSTM dan optimasi menggunakan teknik capung menunjukkan peningkatan akurasi klasifikasi sebesar 97,1% [15].…”
Section: Literature Reviewunclassified